Integrated in silico and in vivo larvicidal evaluation of compounds targeting juvenile hormone for malaria vector control - Eric Kibagendi Osoro; Adeniyi Ayinde Abdulwahab; Florence Ezinwa Nkemehule; Adedoyin John-Joy Owolade; Micheal Abimbola Oladosu; Wilberforce K. Ndarawit; Daramola Oluwasegun Oluwatobiloba; Moses Adondua Abah; Fidelis Ngugi; Njogu M. Kimani; Damilola Samuel Bodun (PLoS ONE, 2026)
Malaria remains a major global health challenge, particularly in sub-Saharan Africa, where it is a leading cause of morbidity and mortality. Inhibition of the mosquito juvenile hormone binding protein (MJHBP) is essential for developing selective and effective insecticides against malaria vectors. We performed virtual screening on 2,874 compounds from Agrochemical Insecticides Library using Python-based workflow in RDKit and Pandas libraries. The resultant compounds were subjected to molecular docking study against MJHBP (pdb:5V13). Further evaluation was performed through molecular mechanics generalized Born surface area (MM-GBSA) analysis, insecticide-likeness assessment, toxicity and environmental hazard predictions and Density Functional Theory (DFT) studies. The top-ranked compounds, together with the co-crystallized ligand, were subsequently subjected to molecular dynamics (MD) simulations. The molecular docking and MM-GBSA analyses identified fifteen lead compounds as potent inhibitors, exhibiting binding affinities ranging from –49.84 kcal/mol to –89.51 kcal/mol, values comparable to that of the co-crystallized ligand (–75.83 kcal/mol). The DFT results of the analysed compounds indicated that the top candidates, based on docking scores and binding energies, possessed lower HOMO-LUMO energy gap values, 1.52 eV for F3023-0929 and 2.36 eV for F2708-0061, compared to the co-crystallized ligand, which had a gap of 3.43 eV. All the top compounds displayed significant insecticidal potential with minimal environmental hazards. The stability of the most promising compounds (F2708-0061 and F3023-0929), identified based on binding free energy, was further corroborated through MD simulation. Further in vivo experiments revealed that F3023-0929 and F2708-0061 exhibited potent larvicidal activity, with LC₅₀ values of 37.75 ppm and 33.49 ppm, respectively, thereby supporting their potential as promising insecticidal candidates for mosquito control.